Identification and evaluation of observational measures for the assessment and/or monitoring of level of consciousness in adult palliative care patients: A systematic review for I-CAN-CARE. (January 2020) - Krooupa, Anna-Maria; Vivat, Bella; McKeever, Stephen; Marcus, Elena; Sawyer, Joseph; Stone, Paddy
Background: The use of observational measures to assess palliative care patients' level of consciousness may improve patient care and comfort. However, there is limited knowledge regarding the validity and reliability of these measures in palliative care settings. Aim: To identify and evaluate the psychometric performance of observational level of consciousness measures used in palliative care. Design: Systematic review; PROSPERO registration: CRD42017073080. Data sources: We searched six databases until November 2018, using search terms combining subject headings and free-text terms. Psychometric performance for each identified tool was appraised independently by two reviewers following established criteria for developing and evaluating health outcome measures. Results: We found 35 different levels of consciousness tools used in 65 studies. Only seven studies reported information about psychometric performance of just eight tools. All other studies used either ad hoc measures for which no formal validation had been undertaken ( n  = 21) or established tools mainly developed and validated in non-palliative care settings ( n  = 37). The Consciousness Scale for Palliative Care and a modified version of the Richmond Agitation–Sedation Scale received the highest ratings in our appraisal, but, since psychometric evidence was limited, no tool could be assessed for all psychometric properties. Conclusion: An increasing number of studies in palliative care are using observational measures of level of consciousness. However, only a few of these tools have been tested for their psychometric performance in that context. Future research in this area should validate and/or refine the existing measures, rather than developing new tools.